Entrepreneurship Integration and Digital Technology in Vocational Education Factors - Naim, Sultono; Barliana, M Syaom; Aryanti, Tutin; Suryadi, Dedy (Journal of Vocational Education Studies, 2025)
There must be an evaluation of new approaches to entrepreneurship in the domain of education in fulfilling the demands of the current era, that is to adapt with the environmental business changes and digital technology that occur in a country. This research aims to study the condition of integration implementation factors in vocational education related to entrepreneurship and digital technology. The method used is quantitative descriptive, including the evaluation research category with data processing and analysis of instrument test such as; validity test, reliability instrument, and then by using Respondent Level Achievement (RLA) technique to analyze the collected data. Research findings of the results and discussions show that the value of variable aspects indicators of vocational education is varied and there tend to be many indicators that still have low value. It indicates that there must be improvement for the school that scores low and development for the school that scores good. The cooperation among schools can become one of alternative solutions to improve the downsides that exist at schools. The schools that score the highest value of aspects/indicators can be best practice for the schools that still have low scores.